Circumventing Brain Barriers: Nanovehicles for Retroaxonal Therapeutic Delivery - Ovsepian, Saak V.; O'Leary, Valerie B.; Ntziachristos, Vasilis; Dolly, J. Oliver (Trends in Molecular Medicine, 2016)
In addition to safeguarding the central nervous system (CNS) from the vast majority of pathogens and toxins, transvascular barriers impose immense challenges to the delivery of beneficial cargo. A few toxins and neurotropic viruses capable of penetrating the brain have proved to be potentially valuable for neuron targeting and enhanced transfer of restorative medicine and therapeutic genes. Here we review molecular concepts and implications of the highly neurotropic tetanus toxin (TeTx) and botulinum neurotoxins (BoNTs) and their ability to infiltrate and migrate throughout neurons. We discuss recent applications of their detoxified variants as versatile nanovehicles for retroaxonal delivery of therapeutics to motor neurons and synapses. Continued advances in research on these remarkable agents in preclinical trials might facilitate their future use for medical benefit.
CRIS-Team Scopus Importer:2023-03-08